Ответ:
у= 9х - 7,5
Пошаговое объяснение:
6х-2у/3=5
-2у/3=5-6х
2у/3=6х-5
у= (6х-5) :
у= (6х-5) *
у= 6х* -5*
у= 9х -
6х-2у/3 = 5
6х - 2у = 5 * 3
6x - 2y = 15
6х = 15 + 2у
х = 15/6 + 2/6у
х = 5/2 + 1/3у
х = 2. 1/2 + 1/3у
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
у= 9х - 7,5
Пошаговое объяснение:
6х-2у/3=5
-2у/3=5-6х
2у/3=6х-5
у= (6х-5) :![\frac{2}{3} \frac{2}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B3%7D)
у= (6х-5) *![\frac{3}{2} \frac{3}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B2%7D)
у= 6х*
-5* ![\frac{3}{2} \frac{3}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B2%7D)
у= 9х -![\frac{15}{2} \frac{15}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B15%7D%7B2%7D)
у= 9х - 7,5
Ответ:
Пошаговое объяснение:
6х-2у/3 = 5
6х - 2у = 5 * 3
6x - 2y = 15
6х = 15 + 2у
х = 15/6 + 2/6у
х = 5/2 + 1/3у
х = 2. 1/2 + 1/3у